Empirical Evidence on the New International Aid Architecture - Danny Cassimon; Stijn Claessens; Bjorn van Campenhout (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2007)
We conduct an empirical study on how 22 donors allocate their bilateral aid among 147 recipient countries over the 1970-2004 period to investigate whether recent changes in the international aid architecture-at the international and country level-have led to changes in donor behavior. We find that after the fall of the Berlin Wall and especially in the late nineties, bilateral aid responds more to economic needs and the quality of a country?s policy and institutional environment and less to debt, size and colonial and political linkages. We also find more selectivity by donors when a country uses a PRSP and passes the HIPC decision point. Importantly, PRSPs and HIPCs reduce the perverse effects of large bilateral and multilateral debt shares on aid flows, suggesting less defensive lending. Overall, it appears certain international aid architecture changes have led to more selectivity in aid allocations. The specific factors causing these changes remain unclear, however. And since there remain (large) differences among donors in selectivity that appear to relate to donors? own institutional environments, reforms will have to be multifaceted.
Keywords: O16; O19; O11; 330; development aid; aid allocation; selectivity; debt relief; HIPC; PRSP; aid architecture